Global analysis of the insulator binding protein CTCF in chromatin barrier regions reveals demarcation of active and repressive domains - Cuddapah, Suresh; Jothi, Raja; Schones, Dustin E.; Roh, Tae-Young; Cui, Kairong; Zhao, Keji (Genome Research, 2009)
Insulators are DNA elements that prevent inappropriate interactions between the neighboring regions of the genome. They can be functionally classified as either enhancer blockers or domain barriers. CTCF (CCCTC-binding factor) is the only known major insulator-binding protein in the vertebrates and has been shown to bind many enhancer-blocking elements. However, it is not clear whether it plays a role in chromatin domain barriers between active and repressive domains. Here, we used ChIP-seq to map the genome-wide binding sites of CTCF in three cell types and identified significant binding of CTCF to the boundaries of repressive chromatin domains marked by H3K27me3. Although we find an extensive overlapping of CTCF-binding sites across the three cell types, its association with the domain boundaries is cell-type-specific. We further show that the nucleosomes flanking CTCF-binding sites are well positioned. Interestingly, we found a complementary pattern between the repressive H3K27me3 and the active H2AK5ac regions, which are separated by CTCF. Our data indicate that CTCF may play important roles in the barrier activity of insulators, and this study provides a resource for further investigation of the CTCF function in organizing chromatin in the human genome.